Raziskave in razvoj sistema za avtomatsko diagnostiko kompresorjev hladilnih aparatov - Potočnik, Primož (Ventil (Ljubljana), 2014)
The development of an automatic diagnostic system for compressors in refrigeration appliances, which is a result of cooperation between the Laboratory of Synergetics at the Faculty of Mechanical Engineering in Ljubljana and the company Gorenje, is presented. The developed diagnostic system consists of a mechatronic unit for automated measurements of the vibrations of compressors, and the control software for the diagnostic analysis of the signals and the transmission of the results to the information system of the company. The system has been successfully tested on the production line of the company and it enables the detection of noisy compressors. By introducing the diagnostic system into industrial operation, the company achieves an increased quality of produced refrigeration appliances in terms of the quality of built-in compressors.
Keywords: avtomatska diagnostika; compressors; hladilni aparati; kompresorji; mechatronic systems; mehatronski sistemi; quality testing; refrigeration appliances; statistical industrial diagnostics; statistična industrijska diagnostika; testiranje kakovosti; vibracije; vibrations